‘Everybody in Nigeria is a doctor…’: a qualitative study of stakeholder perspectives on lay diagnosis of malaria and pneumonia in Nigeria - Elimian, Kelly; Myles, Puja R.; Phalkey, Revati; Sadoh, Ayebo; Pritchard, Catherine (Journal of public health, 2020)
Abstract Background. Lay diagnosis is a widely used diagnostic approach for home management of common illnesses in Nigeria. This study aimed to explore the pers